Environmental management accounting and other environmental/ sustainability related practices: an exploratory case study - Jusoh, Ruzita; Zulkifli, Norhayah; Zainal, Dalilawati; Mokhtar, Norsyahida (Taylor & Francis Group, 2018)
Based on a single case study conducted in a Malaysian chemical company (denoted as Company X), the study explores whether environmental/sustainability practices, which include Environmental Management Accounting (EMA), are implemented in the case company. Data gathered from the review of documentations and in-depth interviews with 12 personnel comprising 10 top and middle level managers from Company X, one officer each from the Department of Environment (DOE) and Department of Safety and Health (DOSH) of Malaysia. Findings show that Company X has implemented a number of environmental/sustainability practices to some extent. Among the environmental-related practices that Company X has engaged with are: waste management, environmental safety, product stewardship, supply chain and distribution, recycling, cost-reduction programmes, carbon-footprint, and life cycle assessment. Findings also reveal that despite having good environmental/sustainability practices, the commitment towards a more systematic measurement and accounting of environmental information (monetary and non-monetary) is still minimal in Company X.